Improving the Role of Employee Engagement: Job-Fit, Organizational-Fit to Intention to Quit (An Evidence from Hospitality Industries) - Adi, Agung Nugroho (Journal of International Conference Proceedings, 2024)
Abstract: This research aims to determine if employee engagement mediates the association between turnover intention, person-job fit (PJ Fit), and person-organization fit (PO Fit). This study employed a survey design involving employees from various hospitality industries in Indonesia. We distributed 470 questionnaires to the respondents (367 are available). SmartPLS 3.0's path analysis was utilized to verify the questionnaires' validity and reliability. Findings. Findings confirmed the direct effect the employee engagement mediates between Person-Job fit and Intention to Quit and Person-Organization Fit and Employee Engagement. In the indirect impact, employee engagement negotiated between Person-Job fit and Intention to Quit, Person-Organization Fit and Intention to Quit. Uniqueness. In the Indonesian hospitality sector, this study clarified the mediating role level of employee engagement between Person-Job fit and Intention to Quit, Person-Organization fit and Intention to Quit. This study also depicts the strength level of the previous model in hospitality industries. Keywords: Person-Job Fit, Person-Organization Fit, Employee engagement, Intention to Quit